(untitled) (The International Journal for Scientific Research, 2026)
This research examines the provisions governing property rights under the Saudi Civil Transactions Law, analyzing the adequacy of its legal framework in regulating and protecting this fundamental real right. It explores how the law balances the owner’s authorities with public interest and third-party rights. Employing a descriptive-analytical and inductive methodology, the study first outlines the concept and characteristics of property rights, then details the three core authorities granted to the owner: use, exploitation, and disposal. It further investigates the legal restrictions imposed on these authorities, including public interest regulations, neighborhood rights, and the prohibition of abuse of right as stipulated in Article 29. In terms of protection, the research reviews the judicial claims available to owners—such as claims for proving ownership, recovery, prevention of interference, and removal of encroachment—as well as the compensation mechanisms based on the principle of full reparation for damages. The study concludes that the Saudi Civil Transactions Law establishes a modern, balanced regulatory framework that safeguards private property while preventing harm to others and ensuring social justice. It highlights the pivotal role of the Saudi judiciary in translating these provisions into effective, practical protection, thereby enhancing legal security and stability in financial and real estate transactions.